DESIGNING DISTANCE LEARNING FOR GROUP THEORY COURSES TO IMPROVE THE 21ST-CENTURY PROFICIENCY OF PROSPECTIVE MATHEMATICS TEACHERS - Mik Salmina; Fitriati; Ahmad Nasriadi (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aimed to produce a distance learning design for the Group Theorycourse to improve the 4C skills of prospective mathematics teachers. Thisresearch is included in Research and Development (R&D), which consists ofthree stages, namely: (1) a preliminary study, (2) development studies, and (3)product effectiveness tests. The research results show that the distance learningdesign developed is feasible and effective for the learning process. Tests Theresearch results are grouped into two parts: (1) tests for aspects of problemsolving and critical thinking skills and (2) non-tests to assess creativity andinnovation, communication, and collaboration. Regarding critical thinkingskills, there are differences in students' critical thinking in distance learningdesigns and group learning theory. However, for problem-solving skills,student problem-solving is the same as distance learning designs in grouptheory learning subjects. For the results of the questionnaire data analysis, it isknown that the indicators for achieving creativity and innovation,communication, and collaboration are above 50%. This shows that the distancelearning design of the Group Theory course has succeeded in increasing theskills of prospective 21st-century mathematics teachers.